Amplifying 23-years insights of Doherty power amplifier: a review and trend analysis / Naufal Adibah Mohd Farid ... [et al.] - Mohd Farid, Naufal Adibah; Md Idros, Mohd Faizul; Halim, Abdul Karimi; Abdul Razak, Abdul Hadi (UiTM Press, 2024)
Scopus database is used in this study to illustrate trends observed on the Doherty Power Amplifier (DPA) using bibliometric data from 2000 to 2023. This study adopts a bibliometric analysis of DPA using Biblioshiny, which comes from the R package of Bibliometrix. The application used in this study would decode information from the Scopus database and convert it into different graphical representations. A variety of DPA viewpoints are investigated, discussed, and found. The results of the bibliometric analysis provide important data on recent and upcoming trend articles in the field of power amplifiers. The analysis also offers significant information on its most productive authors, highly cited documents, keyword analysis results, most productive countries, and thematic map analysis, resulting in several potential research agendas for future studies. Future research is proposed to examine relevant publications in other well-known databases. This study is the first bibliometric study to utilize Biblioshiny to assess DPA trends.